Language Policy and the Construction of Linguistic Identity in the Croatian Educational System - Langston, Keith; Peti-Stantić, Anita (2010)
Authors analyzed the impact of an explicit and implicit language policy to educational system and changes of attitudes among teachers and students in Croatian schools. Although the government in Croatia has been at least partly responsible for promoting the idea of the Croatian language as an important symbol of national identity, we still have a situation in which there is no fully consistent language policy, not even within the educational system. The promotion of orthographic and lexical changes has left many people uncertain as to what should be considered standard, and there is still resistance to abandoning linguistic habits that were well established in the 20th century. However, there is clearly a movement within the educational system to promote spellings, grammatical forms, and lexical items that are symbolically Croatian, which can be seen in official documents such as the national curriculum, programs and materials aimed at Croatian language teachers, and in textbooks ; if these elements are consistently implemented for instruction in all subjects (both in teacher training and in textbooks), they have a good chance of eventual broader adoption within society. Particularly important is the explicit emphasis on language as a symbol of national identity within the newer curricular standards ; the Ministry of Education is clearly promoting a particular language ideology, which if accepted by students in the school system, could affect future development of Croatian language.
Projekt MZOS
ENG